2022
DOI: 10.1186/s12871-022-01829-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of intraoperative hyperglycemia in non-diabetic patients: a prospective observational study

Abstract: Background Intraoperative hyperglycemia has been associated with multiple postoperative complications such as surgical site infection, myocardial infarction, stroke, and death. These complications are not confined to only diabetic patients. However, the incidence of intraoperative hyperglycemia in non-diabetic patients has not been fully elucidated. Additionally, these patients’ risk factors were not well established in previous studies. Methods Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…Perioperative glycemic control plays a significant role in improving surgical outcomes and decreasing morbidity both in patients with or without diabetes mellitus and even in non-cardiac surgeries [6,7]. Nevertheless, intraoperative increases in blood glucose levels and variation can be attributed to various factors [8]. Pain, depth of anesthesia, surgical duration, and drugs that alter blood sugar homeostasis are a few of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative glycemic control plays a significant role in improving surgical outcomes and decreasing morbidity both in patients with or without diabetes mellitus and even in non-cardiac surgeries [6,7]. Nevertheless, intraoperative increases in blood glucose levels and variation can be attributed to various factors [8]. Pain, depth of anesthesia, surgical duration, and drugs that alter blood sugar homeostasis are a few of them.…”
Section: Discussionmentioning
confidence: 99%
“…The data are from a single tertiary care institute and include only patients with ASA physical statuses I and II. In contrast, candidates with a higher ASA physical status risk higher glycemic variability [8]. Although we standardized the depth of anesthesia, we did not keep the continuous data to compare them.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of nondiabetic individuals undergoing moderate- to high-risk surgery experienced intraoperative hyperglycemia. Therefore, the risk factors for intraoperative hyperglycemia must be determined [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…IR is characterized by transient and reversible hyperglycemia, a condition also known as stressful hyperglycemia [40,41]. Recent studies [42,43] have shown that the incidence of postoperative hyperglycemia ranges from 20-40% in patients undergoing non-cardiac surgery. The presence of stress hyperglycemia is often accompanied by perioperative morbidity and mortality, a higher risk of postoperative wound infection, and a longer length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%